PENGARUH SIZE, BOOK TO MARKET RATIO, DAN MOMENTUM TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA - , TOMMY LESMANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study has purposes to analyze the effect of size, book to market ratio, and momentum on stock return of listed companies in Indonesia Stock Exchange. This study was conducted on all companies which listed in Indonesia Stock Exchange in the period of 2007 until 2011. The sampling method on this study is using purposive sampling and the estimation is using multiple regression. The result conclude that all three factor that have been investigating donât have significant effect on the entire stock portfolio return in the Indonesia Stock Exchange. There are some indication that those factors affecting the stock portfolio return, but the effect do not occur in all portfolios, but only in certain portfolio.